Інтерактивні методики навчання у ВНЗ - Козяр, М. М. (НТУ "ХПІ", 2015)
У статті розглядається сутність, використання та методики здійснення інтерактивного навчання студентів у ВНЗ, упровадження інтерактивної стратегії та її впливу на студентів, зміну ролі і функції викладача, а також відповідні переваги та недоліки використання в навчальному процесі.

The article deals with the essence, use and implementation of interactive learning methods of students in higher education, the introduction of an interactive strategy and its impact on students, changing roles and functions of the teacher, as well as the respective advantages and disadvantages of the use in the educational process.
Interactive teaching methods university
Keywords: активне навчання; діалогове навчання; інтерактивні методики; якість освіти; active learning; learning dialog; interactive techniques; quality education